On Sylow Subgroups of Some Shunkov Groups - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study Shunkov groups with the following condition: the normalizer of any finite nontrivial subgroup has an almost layer-finite periodic part. Under this condition, we establish the structure of Sylow 2-subgroups in this group.